Mini invasive transoral approach to the glenoid fossa: Benign lesion removal using endoscopy. (13th February 2015) - Valentini, Valentino; Giovannetti, Filippo; Priore, Paolo; Raponi, Ingrid; Terenzi, Valentina; Cassoni, Andrea
<x xml:space="preserve">Abstract</x> Objective We describe an endoscopic transoral approach for treating benign lesions of the glenoid fossa with or without infratemporal fossa involvement. Study Design Description and validation of surgical technique on living humans. Methods Excision of benign lesions arising from the glenoid fossa was achieved in five patients through a transoral endoscopic approach. Using 0‐ and 45‐degree angled 4‐mm optics, the entire middle skull base and infratemporal fossa were explored without damaging the nearby neurovascular structures. Results Three of the five patients had complete removal of osteochondroma. In the remaining two patients, the lesion removed was diagnosed as osteoma. In one patient, postoperative numbness of the alveolar nerve was observed. No infections were reported. The surgical approach utilized was determined to be valid not only for glenoid fossa exposure but also for management of the middle skull base and infratemporal fossa. Conclusion The described approach to the glenoid fossa offers direct and minimally invasive access to benign lesions within this region. Further use of this approach will allow us to determine its potential in treating malignancies. Level of Evidence 4. Laryngoscope, 125:2054–2057, 2015